The Role of The Sub-District Administrative Organization in Promoting Career Development Projects in Baroh Sub-District, Yaha District, Yala Province - กือนางอ อะห์มัด; เหม ซูนีก้า; อาแด นูรฮายาตี; หลีเส็น อดุลย์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aims to study the roles of the Sub-district Administrative Organization (SAO) in promoting career development projects in Baroh Sub-district, Yaha District, Yala Province, and to explore guidelines for career development project implementation in the area. This study employed a Qualitative Research approach, with 18 key informants, including the SAO President, Clerk, community developers, and local citizens, selected through purposive sampling. Data were collected using Structured In-depth Interviews and analyzed through Content Analysis by categorizing key themes. The researchers ensured data validity through Data Triangulation and presented the findings using Descriptive Analysis. The results revealed that: 1) The Baroh SAO plays a significant role in providing budgetary support, procuring equipment and materials, and offering academic and training assistance, acting as a flexible and accessible supporter across five key dimensions: occupation, religion, tradition, culture, and social welfare. 2) Regarding project implementation guidelines, the SAO does not follow a rigid plan but adaptively modifies projects based on annual community interests and ensures that training schedules are compatible with the local way of life. Furthermore, the study suggests that the SAO should expand market reach from local outlets to broader regional markets and establish a "One Baht a Day" savings group to create a sustainable revolving fund for community careers, while developing a digital database for long-term career development follow-up and evaluation.